Multiple lenders and corporate distress: Evidence on debt restructuring - Antje Brunner; Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
In the recent theoretical literature on lending risk, the coordination problem in multi-creditor relationships have been analyzed extensively. We address this topic empirically, relying on a unique panel data set that includes detailed credit-file information on distressed lending relationships in Germany. In particular, it includes information on creditor pools, a legal institution aiming at coordinating lender interests in borrower distress. We report three major findings. First, the existence of creditor pools increases the probability of workout success. Second, the results are consistent with coordination costs being positively related to pool size. Third, major determinants of pool formation are found to be the number of banks, the distribution of lending shares, and the severity of the distress shock.
urn:nbn:de:hebis:30-30130
Keywords: D74; G21; G33; G34; 330; bank lending; distress; workout; coordination risk